A typology of strategies for user involvement in innovation processes. (1st December 2020) - Storvang, Pia; Haug, Anders; Nguyen, Bang
Abstract : This paper investigates how an organization can involve users in innovation processes. Based on three case studies and the literature on spaces, user-driven innovations and design management, the paper develops a framework that organizes different types of user involvement strategies. The framework aims to provide a rich understanding of how innovative spaces can be staged under different management strategies. To test the framework, nine SMEs from different Danish industries were selected. The findings show that the framework needs to be flexible in order to accommodate how users can be involved in different contexts and stages of the process. In addition, the study demonstrates various approaches to innovative spaces for involving users and their interests in the company. The framework includes a critique of the one-sided promotion of certain innovation paradigms in the literature. As demonstrated in this paper, different contexts require very different innovation approaches.